Nitrogen-decorated carbon dots (NCDs) for thermally conductive smart windows - Tan, Frankie Ting Feng (Nanyang Technological University, 2022)
Heat can be conducted laterally across the surface of a window glass panel through a coating of thermally conductive thin film. The heat will diffuse along the glass panel, towards the heat sink located at the edges. This will lead to a reduction in the cross-sectional conductive heat transfer which will decrease the amount of heat entering from the outside to the inside surface of the window glass panel. This approach is able to provide energy efficient solutions to modern skyscrapers by maintaining a cool temperature without bearing the cost and weight of double or triple glazed glass paned windows. In this research, the thermally conductive thin film was created through carbon dots (CDs) which possess a high thermal conductive property. Subsequently, nitrogen atoms were introduced to the CDs to enhance the high frequency phonons which will improve the lateral thermal conductivity. The synthesis of nitrogen-decorated carbon dots (NCDs) were simply achieved by hydrothermal heat treatment of hydrochloric acid, citric acid and ethylenediamine which is the nitrogen source. These NCDs were mixed with hydroxypropyl methylcellulose (HPMC) and drop casted on a square FTO glass producing a laterally thermally conductive and transparent thin film. This thin film was examined and tested to block high intensity blue light radiation and ultraviolet light (UV). The NCDs thin film was trialled to have a visible light transmission of up to 65%. With the increasing amount of nitrogen atoms in the thermal conductive thin film, it shows a direct increase in the lateral thermal conductivity of the thin film, which suggests the nitrogen is effectively improving the thermal conductivity by concentrating the high frequency phonons.